Strategi Pengendalian Kebakaran Hutan dan Lahan Berbasis Partisipasi Masyarakat di Kecamatan Bengkalis: Community Participation-Based Forest and Land Fire Control Strategy in Bengkalis District - Erzan Syah; Juandi Muhammad; Arifudin Arifudin; Kemal Kemal; Hafidawati Hafidawati; Romie Jhonnerie (JURNAL HUTAN TROPIKA, 2026)
Forest and land fires (karhutla) represent a recurring ecological problem in Bengkalis District, Riau Province. BPBD data records 31 fire incidents during 2021-2025 with a total burned area of 174.75 hectares. This study aims: (1) to evaluate community participation-based fire control efforts; and (2) to formulate a community-based fire control strategy in Sungai Batang Village, Bengkalis District. The study employs a qualitative approach with an instrumental case study design. Data were collected through in-depth interviews with 6 key informants, participatory observation, and document analysis, then analyzed using thematic analysis and SWOT framework. Findings indicate that the fire control system is in a transitional phase from reactive to planned participatory control. Four main strategies are formulated: (1) strengthening inclusive community institutional capacity; (2) developing technology-based communication and information systems; (3) building capacity through structured training; and (4) revitalizing local wisdom. These strategies are mapped into a SWOT matrix across three operational dimensions: prevention, suppression, and post-fire management.